Flowering of Chrysanthemum sp. in pot at various concentrations of corn extract and paclobutrazol. Issue 1 (April 2020) - Ulfa, F; Haring, F; Kanisa, M; Amin, A R; Kasim, N; M Farid, BDR
Abstract: The purpose of this study was to study the effect of application of corn extract and paclobutrazol on the flowering of chrysanthemum ( Chrysanthemum sp) in pots. The research was carried out in a plastic house, Pattapang Village, Tinggi Moncong District, Gowa Regency, South Sulawesi Province, from July to October 2015. The research was conducted in the form of a two-factor factorial using a randomized block design. The first factor was the concentration of corn extract consisted of 0, 50 mL L −1, 100 mL L −1, and 150 mL L −1 . The second factor was paclobutrazol with a concentration consisted of 0, 30 mL L −1, 60 mL L −1 . The results show that application of paclobutrazol 60 mL L −1 gave the shortest stalk length (4.40 cm) and the longest vase life (23.08 days).